Analisis Kinerja Perdagangan Indonesia ke Negara Potensial Benua Afrika - Ade Ayu Fleury Amalina; Tanti Novianti; Alla Asmara (IPB University, 2018)
Trade liberalization generates higher commodity export opportunities between countries. The export opportunities to the African countries are evidenced by the high average growth of the total export values from Indonesia to Africa in 2011-2016, amounting to 5.886%. The aim of this research is to determine the potential importing African countries through the identification of export value and share, evaluate the performance and trade integration between Indonesia and the African countries through RCA, EPD and IIT methods. The results showed that South Africa with commodities like HS 71, 15, 40, 87 and 84 and Egypt with HS 15, 55, 40, 48 and 84, could be potential export destinations for Indonesia in 2011-2016. The Indonesian HS 71, 15 and 40 commodities in South Africa and Egypt i.e. HS 15, 55, 40, and 48, face tremendous competitivity. The potential Indonesian commodities in the South African market with HS codes of 15, 84, and 87 were considered as Falling Star while HS 71 and 40 were in retreating position. The HS 15 and 55 in the Egyptian market were in the position of Falling Star, with HS 40, 48, and 84 in the Retreat position. In South Africa, the HS commodities 71, 15, 40 and HS 87 were weakly integrated while the HS 50 had a strong integration. Keywords: African, RCA, EPD, IIT JEL classification: C23, F10, F13